Contributions of post-mortem studies in the definition of the etiology of Hydrops Fetalis - Carolina Mendonça de Olim (2022)
To determine the contribution of post-mortem studies in the definition of the etiology of hydrops fetalis (HF) and understand its implications in a subsequent pregnancy we retrospectively evaluated 32 fetuses with HF. In cases with prenatal diagnosis, a comparison between etiology determinate in the prenatal period and after post-mortem study was performed. The post-mortem study added information in 24 (75%) cases. Autopsy allowed the diagnosis of five new cases, detection of DNA of infectious agent allowed diagnosis of infection in four (66.7%) cases, and genetic studies diagnosed three new cases of chromosomal anomalies. In cases with prenatal diagnosis (27, 84.4%), the post-mortem study reclassified the etiology in 10 (37%) cases, without statistical differences. Even though no statistical differences were found, the post-mortem studies are essential in the approach to HF once it provides information that can be considered while making an informed choice regarding a possible future pregnancy.